The Medical Literature Analysis and Retrieval System (MEDLARS) of the U.S. National Library of Medicine - Taine, S. I. (Methods of Information in Medicine, 1963)
MEDLARS is an acronym for the name (Medical Literature Analysis and Retrieval System) which the National Library of Medicine has given to the computer-based bibliographic retrieval and publication system now under development. From the bibliographic viewpoint, MEDLARS embraces the following general objectives: Increased coverage of the current substantive medical literature of the world up to totality; deeper subject analysis of, and broader accessibility to, the bibliographic items aided by additional avenues of approach such as language, and geographic origins of the document; more rapid processing to accelerate the availability of the information contained in the system; the capture and delivery of pinpointed and prescribed segments of the total file in a variety of patterns of selection and arrangement. The paper describes the history, aims and products of the new system.MEDLARS ist eine Kurzbezeichnung für den Namen (Medical Literature Analysis and Retrieval System) des elektronischen bibliographischen Dokumentations- und Publikationssystems, das die National Library of Medicine zur Zeit vorbereitet. Vom bibliographischen Gesichtspunkt aus handelt es sich dabei um folgende allgemeine Zielsetzungen: verbesserte Erfassung und Auswertung der wesentlichen medizinischen Gegenwartsliteratur aller Länder, wobei möglichst weitgehende Vollständigkeit angestrebt wird; intensivere und weitgehendere sachliche Erschließung der bibliographischen Einheiten mit Hilfe zusätzlicher Kennmerkmale, wie etwa Originalsprache und Herkunftsland des betreffenden Dokuments; schnellere Verarbeitung des Datenmaterials, um die Verfügbarkeit der im System gespeicherten Informationen zu beschleunigen; die jeweilige Erfassung und Ausgabe bestimmter und vorgeschriebener Abschnitte des Speichermaterials in verschiedener Auswahl und Anordnung. Werdegang, Ziele und zu erwartende Ergebnisse des neuen Systems werden beschrieben.